Childhood Obesity. Issue 1 (January 2016) - Beal, Judy A.
Abstract : Childhood obesity is a major public health problem that has immediate and long-term sequelae including: high cholesterol or high blood pressure, diabetes, bone and joint disorders, sleep apnea, and social and emotional problems. Obese children and adolescents are highly likely to remain obese as adults and therefore develop serious adult health problems of diabetes, heart disease, stroke, cancer, and osteoarthritis. Our pediatric nursing expert, Dr. Beal, provides an update.